Brachial Plexus Injury: Recent Diagnosis and Management - Sumarwoto, Tito; Suroto, Heri; Mahyudin, Ferdiansyah; Utomo, Dwikora Novembri; Hadinoto, Seti Aji; Abdulhamid, Muhammad; Utomo, Pamudji; Romaniyanto, Romaniyanto; Prijosedjati, R. Andhi; Rhatomy, Sholahuddin (Open Access Macedonian Journal of Medical Sciences, 2021)
Brachial plexus injury is known to be one of the most serious upper limb injuries, causes paralysis of the upper limbs and changes in activity of daily living, with the consequence disruption of activity of daily living, socio-economic problems, depression, and hopelessness. Management must be done properly. The evaluation and examination consist of detailed anamnesis on chronological events, complete physical examination, imaging studies, and electrophysiology study. Management can be done nonsurgically and surgically. Knowledge of the history of injury, timing of surgery, priority in restoring function, and managing patient expectations are important concepts in treating patient with brachial plexus injury. Timing is a very important thing. The results of these interventions vary depending on several parameters. Recognizing the basic principles of managing brachial plexus injuries is indispensable for all clinicians who treat these injuries.